Խորագետ Հայրապետը. Գարեգին Ա. Ամենայն Հայոց Կաթողիկոսը (կենսագրական ակնարկ) - Բալոյեան, Հրաչեայ (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Католикос Всех Армян Гарегин I — один из признанных деятелей Армянской и общехристианской Церкви, ученый, мыслитель, публицист, педагог, культурный деятель. Он осуществлял эффективную церковную, национальную и благотворительную деятельность в Армении и за рубежом, активно поддерживал армянское книгопечатание, выступал организатором культурной жизни Армении. До избрания Католикосом Всех Армян Гарегин I имел тесные связи с родиной, в частности с Первопрестольным Святым Эчмиадзином. Он оказывал большую материальную и моральную поддержку армянам в Армении и за рубежом. Осуществлял проармянскую деятельность в диаспоре. Как Католикос, все свои силы и энергию он направлял на регулирование и организацию церковной жизни. Он проделал значительную работу для развития армянской культуры, внес большой вклад в дело церковного строительства, вел интенсивную экуменическую деятельность и был одним из видных деятелей межцерковного движения. Гарегин I был одним из наших интеллигентных католикосов, занимался наукой и преподавательской деятельностью. Любил книги. Его армянский был богат и красив. Исследования, размышления, заветы и проповеди Католикоса были изданы отдельными книгами. За свое преданное служение церковным и национальным интересам он снискал большую любовь и уважение армянского духовенства, интеллигенции и народа, благодаря своим высоким интеллектуальным дарованиям и профессиональной подготовке он пользовался любовью и уважением церковнослужителей и интеллигенции за рубежом. О нем, его трудах и достижениях написаны книги. Catholicos Karekin I of All Armenians is one of the recognized figures of the Armenian and the universal Christian church: scientist, thinker, publicist, pedagogue, cultural figure. He carried out effective ecclesiastical, national and philanthropic activities in Armenia and abroad, greatly supported Armenian publishing, acted as an organizer of Armenian cultural life. Before being elected the Catholicos of All Armenians, Karekin I had close ties with the Motherland, particularly with the Mother See of Holy Etchmiadzin. He provided great material and moral support to the Armenians in Armenia and abroad. He stimulated pro-national activities in the Diaspora. As the Armenian Catholicos, he directed all his efforts and energy to the internal regulation and organization of the church life. He has done a significant work for the development of the Armenian culture. He made a great contribution to the church building field. Carrying out rapid ecumenical activity, he was one of the prominent figures of the inter-church movement. Karekin I was one of our intellectual catholicoi, engaged in science and teaching. He had a cult of books. His Armenian language was rich and beautiful. The researches, reflections, oracles and sermons of the Catholicos were published in separate books. He received great love and respect from the Armenian priesthood, intellectuals and the people for his ecclesiastical and national activities and enjoyed the love and respect of foreign churchmen and intellectuals for his high intellectual abilities and professional preparation. Books have been written about the hero of our review, his work and merit.
Keywords: Հաղորդումներ; Կենսագրութիւն